Chikungunya Infection and Immunity: An Overview - Verma, Priyanka; Sharma, Alpana; Shankar, Hari; Rao, Donthamsetty N. (Current Immunology Reviews (Discontinued), 2018)
Background: Chikungunya infections are a major concern because of their persistent recurrence in the last few decades. Chikungunya virus (CHIKV) is a mosquito borne alpha virus that causes an acute febrile illness accompanied by body rashes, myalgia and polyarthralgia; which may persists for years. Chikungunya fever, affect millions of people in Africa, Asia, including the Indian subcontinent and lately in several regions of the Americas. No specific antivirals and vaccines are currently available to treat or prevent the disease. Methods: Understanding the mechanisms of host immune responses to CHIKV and the immunopathology of the disease is essential for the development of vaccines and diagnostics. Many studies have demonstrated the role of the immune response in the immunopathology of the disease and in the host's incapability to clear the virus efficiently. In this review the excellence of the referenced papers were evaluated using standard tools. Results: Total seventy-four papers were included in the review. Majority of them were highlighted the importance of understanding the immunopathology of virus, contributing factor and control measures of the epidemics. Nineteen papers were provided the current occurrence and re-emergence of the disease. The diagnostic importance (sensitivity and specificity) of developed diagnostics for the early detection were also provided in eight papers. Conclusion: In the current review we highlighted the importance of conceptual mechanism of the host immune responses to CHIKV and the immunopathology of this alpha virus. The presented review provides an update on the infection, its vector, and the disease transmission, research development, and administration for avoidance of Chikungunya disease.
Keywords: infection